Mouse and Fly Sperm Motility Changes Differently under Modelling Microgravity. - Ogneva, I.V. (Current Issues in Molecular Biology, 2021)
Sperm motility is essential for the natural fertilization process in most animal species. Despite the fact that evolution took place under conditions of constant gravity, the motility of spermatozoa of insects and mammals under microgravity conditions changes in different ways. In this work, an attempt was made to explain this effect. The sperm motility of the fruit fly Drosophila melanogaster and the mouse was evaluated after exposure to a random positioning machine for 6 h. Sodium fluoride was used to inhibit serine/threonine phosphatases, sodium orthovanadate was used to inhibit tyrosine phosphatases, and 6-(dimethylamino)purine was used to inhibit protein kinases. The results obtained indicate that simulated microgravity leads to an increase in the speed of movement of fly spermatozoa by 30% (p < 0.05), and this effect is blocked by sodium fluoride. In contrast, a 29% (p < 0.05) decrease in the speed of movement of mouse spermatozoa under simulated microgravity is prevented by 6-(dimethylamino)purine. Moreover, after 6 h of exposure, the content of tubulin cytoskeleton and actin proteins remains at the control level in the spermatozoa of flies and mice. However, the content of the actin-binding protein alpha-actinin in fly sperm decreases by 29% (p < 0.05), while in mouse sperm, the relative content of alpha-actinin1 increases by 94% (p < 0.05) and alpha-actinin4 by 121% (p < 0.05) relative to the control, as determined by 6 simulated microgravity tests. It can be assumed that the effect of simulated microgravity on the motility of mammalian spermatozoa is mediated through the regulation of phosphorylation and that of insects through the regulation of dephosphorylation of motor proteins; moreover, the development of a response to changes in external mechanical conditions has a different time scale.